IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH SHORT DRAMA - Yuniwati, Ribkah; Wijaya, Bambang; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims to improve the students’ speaking ability through short drama. Based on the writer experience during teaching, the students find difficulty to get ideas and how to pronounce the dialogue of short drama. The methodology of this research is a classroom action research which consisted of 3 cycles. The research was conducted at SMP DIAN SEBADU in the academic year 2013/2014. The subject of this research was the eighth grade students. The number of participants in this research was 30 students. The result of this research has shown that the students’ progress in improves speaking in each cycle. First cycle was 5.2 point (less than 70, not achieved). The second cycles was 6.2 point (less than 70, not achieved). The third cycle was 7.1 point (Achieved) which was higher than the KKM score. In conclusion, the use of short drama had a value in improving the students’ speaking ability. Key Word: Improving Students’ Speaking Ability Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan berbicara siswa melalui drama pendek. Berdasarkan pengalaman penulis selama mengajar, siswa-siswa menemukan kesulitan dalam menemukan ide-ide dari drama pendek dan cara mengucapkan percakapan dari drama pendek tersebut. Metode penelitian ini adalah penelitian tindakan kelas yang terdiri dari tiga siklus. Penelitian ini dilaksanakan di SMP DIAN SEBADU tahun pelajaran 2013/2014. Subyek dari penelitian ini adalah siswa-siswi kelas VIII yang berjumlah 30 siswa. Hasil penelitian ini pada siklus pertama poin siswa 5.2 (kurang dari 70, tidak tercapai). Hasil siklus kedua poin siswa 6.2 (kurang dari 70, tidak tercapai). Hasil siklus tiga poin siswa 7.1 (tercapai) dimana lebih dari KKM. Dapat disimpulkan, penggunaan drama pendek dapat meningkatkan kemampuan berbicara siswa. Kata Kunci: Meningkatkan Kemampuan Berbicara Siswa